Enrolling advisers in governing privatised agricultural extension in Australia: challenges and opportunities for the research, development and extension system. Issue 3 (27th May 2017) - Paschen, Jana-Axinja; Reichelt, Nicole; King, Barbara; Ayre, Margaret; Nettle, Ruth
ABSTRACT: Purpose: Current developments in the Australian agricultural research, development and extension (RD&E) system exemplify the complex governance challenges arising from the international privatisation of agricultural extension. Presenting early challenges emerging from a multi-stakeholder project aimed at stimulating the role of the private advisory sector in the RD&E system, this paper contributes to understanding change dynamics in the RD&E system. Methodology: The project applies action research to assist reframing current RD&E governance arrangements towards an enhanced, pluralistic and collaborative system. This paper uses multi-level transition theory (MLP) to explore the dynamics of change by describing the 'regime' of the current Australian RD&E system, wherein the project is an emergent 'niche-in-the- making'. Findings: The regime-based challenges arising from the unfolding Australian project collaboration allow critical assessment of the first moves of niche formation initiated by the project. Initial findings suggest a persisting instrumentalist conceptualisation of the private sector's role in the RD&E system solely as extension providers. This is in tension with the project vision of supporting new roles for private sector advisers as key actors in the governance of co-innovation processes. Practical implications: In describing these challenges and considering how the project's action research can facilitate participant responses, we contribute to understanding how niche formation can be supported in Australia and internationally. Theoretical implications: The paper contributes to a research agenda related to the governance of agricultural advisory services via an analysis of social practice elements that constitute internal niche processes. Originality: Enabling critical analysis of the incumbent regime of the current RD&E system, this framework provides insights into how niche responses aimed at the RD&E system change can be supported.